PERFORMANCE ANALYSIS OF SINGLE FLASH GEOTHERMAL POWER PLANTS - Dagdas, Ahmet (YILDIZ TECHNICAL UNIV, 2005)
Single flash geothermal power plants are the most commonly used plants for power generation from liquid dominated geothermal reservoirs. There are numerous single flash geothermal power plants all over the world. The single flash power plants can be installed over high temperature geothermal reservoirs and they have low first and second law efficiencies. The main reason of low conversion efficiency is lower pressure and temperature values of geofluid. In this paper, performance analysis methods are deliberated of single flash geothermal power plant. A hypothetical single flash power plant has been designed for a geothermal reservoir that ensured geofluid of 210 degrees C and 200 kg/s. According to results, optimum flashing pressure has been determined of 250 kPa and overall first and second law efficiencies have been calculated as 5.34% and 22.35%, respectively.
Keywords: Geothermal; Power plant; Exergy; Power production; Engineering